The implications of intellectual capital on performance measurement and corporate performance - Sofian, Saudah; Tayles, Mike; Pike, Richard (Fakulti Pengurusan dan Pembangunan Sumber Manusia, 2006)
The traditional performance measures fail to capture and monitor multiple dimensions of performance; they concentrate almost only on financial aspects of the organizations. Intellectual capital (IC) gives rise to benefits that are hard to quantify, such as management, customer retention, R&D, and innovation. These benefits are not captured by the traditional measures. This suggests that they are not adequate for the current information age, which encompasses new business environment and realities. This paper examines the impact of the degree and form of IC on management accounting practices, specifically, performance measurement and corporate performance. We explore whether firms investing heavily on IC are more likely to emphasise non-financial measures. We also examine whether the degree of IC values in these firms influence their performance. The paper reports the results of a study conducted through a survey in over 100 large companies covering both high and low levels of IC. The study explored both the role of management accounting information and that of the management accountant. Results suggest some evolution in performance measurement approaches due to the impact of IC and they also indicate that IC does influence corporate performance